Bridging the Gap: Improving Locum Rates at South West London and St George’s Mental Health NHS Trust - Tamara Clarke (BJPsych Open)
Aims: The 2023 GMC national trainee survey revealed that 33% of secondary care trainers reported that their trainees’ education and training were adversely affected because rota gaps aren’t always dealt with appropriately. This project aimed to improve locum rates within the South West London and St George’s Mental Health NHS Trust (SWLSTG) to address these issues and enhance training conditions.